PENGEMBANGAN MULTIMEDIA INTERAKTIF IPS KELAS VII MATERI KERAGAMAN BENTUK MUKA BUMI - Hamidah Nurjamilah; Sudjawo Sudjarwo; Herpratiwi Herpratiwi (Jurnal Studi Sosial / Journal of Social Studies, 2013)
The background of research and development based from difficulty faced by the student grade VII to understanding the variety of earth superficies chapter. The aim of this research are to obtain multimedia interactive as one of learning media in studying social studies, to analysis benefit of effectiveness the development multimedia interactive and to analysis perception from the learners and teachers towards multimedia interactive applied to learning social studies. Research and cultivation based on RD Borg and Gall. This result has been evaluated by material subject proficient, multimedia proficient, the teacher as practitioner and three students. Result data from that evaluation have analyzed descriptively. Whereas how to know of effectiveness this product are by pre-testpost-test experiment model. Data from pre-testpost-test above then have analyzed through ratio gain normalized and test result. Result from this research and development are the appraisal from the proficient for development result multimedia interactive can be used in the learning process of social studies, social studies learning using interactive multimedia more effective than conventional learning, feedback from the teacher and student to developed interactive multimedia can help and facilitate the understanding of concepts in the variety of earth superficies chapter.Keywords : multimedia, interactive, earth, diversity.